IDENTIFIKASI JENIS TENGKAWANG (Shorea spp) SEBAGAI PEWARNA ALAMI TENUN IKAT KABUPATEN KAPUAS HULU KALIMANTAN BARAT - Eni, Anggelia; Dewantara, Iswan; Sisillia, Lolyta (JURNAL HUTAN LESTARI, 2018)
Tengkawang (Shorea spp) is one type of forestry plant that grows in tropical rain forest. The existence of tengkawang in its natural habitat is now beginning to decrease and hard to find. Communities in Tekalong Village Lanjak Deras Village Batang Lupar Sub-district, Kapuas Hulu Regency utilizes tengkawang (Shorea spp) as a natural dye ikat. Tengkawang leaf in traditional though to produce a dye that is on the stew. This study aims to obtain data on identification and describe the characteristics of morphology tengkawang (Shorea spp), and to know the utilization of tengkawang (Shorea spp) by the community in Tekalong Village. The results of identification found 2 types of tengkawang is Shorea macrophylla 49 stem dan Shorea splendida 13 stem, Part of tengkawang that is used by the community as a natural dye that is old leaf.Keywords: identification, natural dyes, Tengkawang (Shorea spp) weaving ikat.